Analysis of the qur'anic methodology of da'wah for the contemporary western context - Karimian, Nasser (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International islamic University Malaysia, 2020)
Although the Western world has historically been associated with Christianity, statistical evidence suggests that the traditional religious roots from which the Western civilization emerged are taking a backseat to secular ideologies, namely, atheism and agnosticism. As these ideologies continue to spread, the Muslim population in the Western world continues to increase due to immigration from Muslim countries, the high birth rates of Muslim families, and conversion to Islam. As Muslims become increasingly exposed to these proliferating ideologies, it becomes incumbent upon Muslim scholarship to defensively address the doubts raised by these views in an attempt to preserve the faith of the more impressionable devotees, while simultaneously educating them on how to proselytize and spark interest in Islam. This research seeks to analyze the intellectual credibility of these beliefs from the Qur'anic perspective, while extracting necessary lessons that are helpful to the average Western Muslim on how to approach a non-Muslim. The objective is to extract Qur'anic answers to the growing doubts of both atheism and agnosticism in their various forms, while simultaneously deriving lessons from two of the most frequently mentioned architypes of proselytization: Noah ﷺ and Abraham ﷺ. The Qur'an frequently recounts the conversations they had with their obstinate communities, thus providing us with insight into the divine wisdom as conveyed by the Almighty's Messengers, which is then interpreted by the author and elucidated upon, thus making it relevant for a modern audience.